2(-7k+4)=-13

Simple and best practice solution for 2(-7k+4)=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-7k+4)=-13 equation:


Simplifying
2(-7k + 4) = -13

Reorder the terms:
2(4 + -7k) = -13
(4 * 2 + -7k * 2) = -13
(8 + -14k) = -13

Solving
8 + -14k = -13

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -14k = -13 + -8

Combine like terms: 8 + -8 = 0
0 + -14k = -13 + -8
-14k = -13 + -8

Combine like terms: -13 + -8 = -21
-14k = -21

Divide each side by '-14'.
k = 1.5

Simplifying
k = 1.5

See similar equations:

| 2t^2-16r=0 | | -0.9=-5.7 | | P(x+1)=-2 | | -2(d-9)=3d+14 | | e/23= | | Cos^2x-4cosx=10 | | 9/x=15/32 | | 40(x^2-1)=39x | | 5=5(4-1)/3 | | 10/9×21 | | 21=27x | | -y-15x=-27 | | X^3-4x=15.2 | | 9x-8+8=180 | | 21-6x=-4x+3(7-7x) | | 3.5x=-10 | | 6a-2b+c= | | 3xy(7x+4y)= | | -14=8.4+7m | | 21-6x=-4x+3(21-21x) | | 4r=6+5r | | -11x=-2x+45 | | 1.2-x=-1.7 | | 3(u-2)-3=-2(-8u+3)-7u | | 20s+20s= | | 3x+x+4x=96 | | 25+.91b=47 | | 2tan(x)=-2 | | 10x+3=31 | | X+3.4=11.6 | | 149=13x+5 | | 4(a+3)=-3(a-1)+31 |

Equations solver categories